PERBANDINGAN MENGONSUMSI BERBAGAI JENIS MINUMAN BERKAFEIN (KOPI, TEH HIJAU, DAN MINUMAN BERENERGI) TERHADAP WAKTU REAKSI - Wigit Kisworo; Hamidie Ronald Daniel Ray; Ugelta Surdiniaty (JURNAL ILMU FAAL OLAHRAGA INDONESIA, 2021)
Generally, the aim of this research to know the comparison of caffeine drinks through the result of reaction time after consumption coffee, green tea, and energy drink by the same amount of caffeine. The way to gather the data is using purposive sampling, the population that chosen by the researcher is 10 respondents’ college students of Ilmu Keolahragaan batch 2016. For data analysis, using SPSS 21 program for windows and Statistical calculation that used is One-Way ANOVA continues with Post Hoc Tukey. The average result from time reaction on Speed Anticipation Reaction is 1.263 (placebo), 1,257 (green tea), 1.271 (energy drink), and 1.358 (black coffee). For Body Reaction Time Test (visual) shows the average around 1.239 (placebo), 0.245 (green tea), 0.257 (green tea), and 0.244 (black coffee). While on Whole Body Reaction Time Test (auditory) shows the average0.239 (placebo), 0.239 (green tea), 0.274 (energy drink), and 0.263 (black coffee). The signification value from three-time reaction test are (Speed Anticipation Reaction Sig. 0.706 > 0.05, Whole Body Reaction (visual) Sig. 0.877 > 0.05, and Whole Body Reaction (auditory) Sig. 0.348 > 0.05) all of the result above 0.05. Hence, it can be concluded there is no significant difference through time reaction result after consumption kind of caffeine drinks with the same concentration.